Disfluencies in 5.1 to 6 Year Old Kannada Speaking Children - Anjana B.Ram; Savithri S.R. (Journal of All India Institute of Speech and Hearing)
Speech samples of 20 Kannada speaking children were analyzed to identify the disfluencies. Frequency and types of disfluencies and the effect of gender on disfluencies were analyzed Results showed that majority of the children had almost all the disfluency types. The most prominent disfluency type was sound repetitions. Also, boys, in general, showed greater percentage of disfluencies compared to girls.